Solve for x (complex solution)
x=-\frac{36i\sqrt{-97\left(±2\right)}}{97}
x=\frac{36i\sqrt{-97\left(±2\right)}}{97}
Solve for x
x=\frac{36\sqrt{97\left(±2\right)}}{97}
x=-\frac{36\sqrt{97\left(±2\right)}}{97}\text{, }\frac{5184\left(±2\right)}{97}\geq 0
Graph
Share
Copied to clipboard
16x^{2}+81x^{2}=1296\left(±2\right)
Multiply both sides of the equation by 1296, the least common multiple of 81,16.
97x^{2}=1296\left(±2\right)
Combine 16x^{2} and 81x^{2} to get 97x^{2}.
x^{2}=\frac{1296\left(±2\right)}{97}
Dividing by 97 undoes the multiplication by 97.
x=\frac{36\sqrt{97\left(±2\right)}}{97} x=-\frac{36\sqrt{97\left(±2\right)}}{97}
Take the square root of both sides of the equation.
16x^{2}+81x^{2}=1296\left(±2\right)
Multiply both sides of the equation by 1296, the least common multiple of 81,16.
97x^{2}=1296\left(±2\right)
Combine 16x^{2} and 81x^{2} to get 97x^{2}.
97x^{2}-1296\left(±2\right)=0
Subtract 1296\left(±2\right) from both sides.
x=\frac{0±\sqrt{0^{2}-4\times 97\left(-1296\left(±2\right)\right)}}{2\times 97}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 97 for a, 0 for b, and -1296\left(±2\right) for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{0±\sqrt{-4\times 97\left(-1296\left(±2\right)\right)}}{2\times 97}
Square 0.
x=\frac{0±\sqrt{-388\left(-1296\left(±2\right)\right)}}{2\times 97}
Multiply -4 times 97.
x=\frac{0±\sqrt{502848\left(±2\right)}}{2\times 97}
Multiply -388 times -1296\left(±2\right).
x=\frac{0±72\sqrt{97\left(±2\right)}}{2\times 97}
Take the square root of 502848\left(±2\right).
x=\frac{0±72\sqrt{97\left(±2\right)}}{194}
Multiply 2 times 97.
x=\frac{36\sqrt{97\left(±2\right)}}{97}
Now solve the equation x=\frac{0±72\sqrt{97\left(±2\right)}}{194} when ± is plus.
x=-\frac{36\sqrt{97\left(±2\right)}}{97}
Now solve the equation x=\frac{0±72\sqrt{97\left(±2\right)}}{194} when ± is minus.
x=\frac{36\sqrt{97\left(±2\right)}}{97} x=-\frac{36\sqrt{97\left(±2\right)}}{97}
The equation is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}